Economic Shifts in India Due to COVID-19: An In-Depth Look at the Pre and Post-Pandemic Conditions Highlighting the Farmer's Perspective - , Niyati Thakur; , Srinatha T N; Prashant,; , Manish K L; , Atul Chaudhary; , Pramod Kumar; , Shreya S Hanji; , Popavath Bhargav Naik (Archives of Current Research International, 2024)
In 2019-20, the global economic sky overcasted with COVID-19, a virus of the size of 0.12 microns. The global pandemic has produced a variety of unanticipated shocks to the economies around the world. It adversely affected the Indian economy also. The year 2021 has commenced with both hope and fear – several parts of the world are locking down and bracing against new waves of infections and speedily communicable mutations. The main objective of this study is to explore the impact of the novel coronavirus pneumonia on the economy of India and the government response to it. The pandemic has drastic impact on different aspects of economy – GDP, GVA, agriculture, trade, employment, service, industry. India’s GDP growth rate faced a drastic decline of -7.25 per cent in FY 2020-21 as compared to previous year, with a V shaped recovery. Due to the restrictions imposed by the government, the availability of agricultural inputs decreased leading to the hike in the prices. The agricultural producers throughout the country faced various marketing problems. Also, the farmers of Himachal Pradesh were also affected in various terms. Based on a survey among smallholder farmers of Himachal Pradesh, it was concluded that the main impact of the pandemic was witnessed by lack of financial assistance, restricted movement during marketing of produce, packaging problem and postharvest loss of the produce. The growth rate change (Y-O-Y) in 2020-21 over 2019-20 in different sectors of Indian economy declined, including GVA (-6.61), agriculture (3.63), industry (-6.37%), service (-8.38) and GDP (-7.25). In 2020, unemployment was high from April (23.52 %), May (22.75 %) and June (10.10 %) due to the lockdown, whereas, during 2021, it was higher in May (11.84%) and June (9.17%) months. The pandemic has negative impact on trade as depicted by the Y-O-Y per cent change in export and import during 2019-20 (-5.06%) and 2020-21 (-6.88%). The central and state governments have recognized the challenge and have responded and the policy makers need to be prepared to scale up the response so as to minimise the impact of the shock on all the sectors and pave the way for a V-shaped recovery.